2008
DOI: 10.1063/1.2918125
|View full text |Cite
|
Sign up to set email alerts
|

Increased efficiency of short-pulse laser-generated proton beams from novel flat-top cone targets

Abstract: Ion-driven fast ignition (IFI) may have significant advantages over electron-driven FI due to the potentially large reduction in the amount of energy required for the ignition beam and the laser driver. Recent experiments at the Los Alamos National Laboratory’s Trident facility employing novel Au flat-top cone targets have produced a fourfold increase in laser-energy to ion-energy efficiency, a 13-fold increase in the number of ions above 10MeV, and a few times increase in the maximum ion energy compared to Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…Also, several ideas on target design to generate high-quality, high-efficiency and high-energy protons have been proposed. Flippo et al used flat-top cone targets to get high-efficiency proton beams [8]. By using particle-in-cell (PIC) simulations, Liu et al showed that energetic collimated ion bunches can be achieved with a thin concave target [9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, several ideas on target design to generate high-quality, high-efficiency and high-energy protons have been proposed. Flippo et al used flat-top cone targets to get high-efficiency proton beams [8]. By using particle-in-cell (PIC) simulations, Liu et al showed that energetic collimated ion bunches can be achieved with a thin concave target [9].…”
Section: Introductionmentioning
confidence: 99%
“…This scheme, however, suffers from a number of severe drawbacks [11], including (i) a disfavorable scaling of achievable ion energies with increasing laser intensity [12], limiting the scheme's efficiency at higher laser intensities, (ii) a limited control over the acceleration, as is apparent from the mostly thermal ion energy spectrum, hindering the precise tuning of the target ion energies, as well as (iii) a low efficiency of the acceleration mechanism at high laser powers [13]. Many of these drawbacks, however, can be counteracted to some extent by specially designed targets [14][15][16][17] and laser pulse shapes [18,19]. Thus, the comparatively simple design and operation of TNSA accelerators renders it a promising mechanism for the construction of reliable and stable lower-energy laser ion-accelerators.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have recently been performed of specially designed targets and laser pulse shapes [23][24][25][26][27][28][29][30][31][32][33][34][35]. However, it is well known that the TNSA scheme has several shortcomings, such as intrinsic angular and energy spread of the accelerated ions.…”
Section: Introductionmentioning
confidence: 99%